Джерела київських рельєфів зі "світськими" сюжетами: питання атрибуції та датування - Архипова, Є.І. (Археологія і давня історія України, 2022)
Статтю присвячено атрибуції серії київських
рельєфів з пірофілітового сланцю зі світськими або
невизначеними сюжетами, іконографія та датування яких є предметом дослідження не одного покоління вчених. Рельєфи знайдено вже пошкодженими або
використаними вдруге, тому їхнє початкове розміщення — інтер’єр або фасад, храм чи палац — також залишається дискусійним. Вивчення зображень цих рельєфів у контексті розвитку візантійського
мистецтва, проте, свідчить, що київські майстри
копіювали християнські зразки, формування яких
відбувалося під впливом античної спадщини та поєднувало світські, міфологічні та біблійні сюжети. За іконографією та стилем київські є творами другої половини ХІ — початку ХІІ ст. The earliest Kyiv reliefs with figurative images
correlate with temples built in the second half of the
11th — early 12th centuries. The iconography and dating
of Ovruch pyrophyllite slate reliefs with secular
or indefinite plots has been the subject of research by
more than one generation of scholars. The reliefs have
been found already damaged or reused, so their original
placement in the interior or faзade, as well in the
temple or palace also remains a matter of debate.
The study of the images of these reliefs in the context
of the development of Byzantine art shows that the
Kyiv artists copied a Christian patterns that combined
secular, mythological and biblical plots, the formation
of which took place under the influence of the Classic
heritage. According to the conditions of discovery, iconography
and style, these are the works of the second
half of the 11th — early 12th centuries. The typological
and stylistic similarity of four such reliefs permit
to suggest that they were made for the same building,
although they were found in different parts of the city.
They depict the biblical character Samson or David,
the mythological character Cybele or the Great Mother
of the Gods, a warrior fighting the lion and a fragment
of the animal head — a goat or a lioness. Fragments
of two other reliefs depict the animal looks like a lion
with the rider on its back, possibly Samson or David.
The depiction of a man riding a beast is the motif of oriental
origin that became widespread in Byzantine and
Romanesque art of the 12th century, including in Rus.
Two fragments of slabs depicting the griffin in high
relief come from the exterior decor. In the art of the
10th—12th centuries, the griffin as a vigilant guard of
the sacred place was depicted on the facades of churches
in the type of «solemn procession». The Kyiv’s griffin
was probably included in the heraldic composition. The
question of the placement of the slabs — in a palace or
a temple — is still disputable.